Effectiveness of Providing Brain Gym on Gross Motor Development in Preschool Children - Adzani, Nursalimah Agistina; Awanis, Almas; Ariyanti, Lilik (Universitas Muhammadiyah Surakarta, 2024)
Introduction: The golden period is the early life of a child where at the age of 0-5 years there is a very rapid brain development that affects motor development. The importance of motor development stimulation can improve and optimize growth and development, one of the stimulations that can be given is brain gym: The golden period is the early life of a child where at the age of 0-5 years there is a very rapid brain development that affects motor development. The importance of stimulating motor development can improve and optimize growth and development, one of the stimulations that can be given is brain gym. To analyze the effectiveness of brain gym on gross motor development of preschool children. Methods: This research design is a pretest-posttest group design with a control group. The sample was preschool children aged 4-6 years totaling 34 people consisting of intervention group (15 people) and control group (19 people). The gross motor measurement instrument used the Test of Gross Motor Development-2 (TGMD-2) technique. Brain gym was given 2 times per week for 4 weeks. Results: The mean TGMD-2 score of the intervention group increased after being given brain gym by 1.17 points. The mean TGMD-2 score of the control group also increased by 0.16 points. The Man Whitney analysis results showed a p-value of 0.00 (value <0.05). Conclusion: Brain gym is effective in improving the gross motor development of preschool children.